Beyond Absenteeism: Father Incarceration and its Effects on Children’s Development - Amanda Geller
High rates of incarceration among American men, coupled with high rates of fatherhood among men in prison, have motivated recent research on the effects of parental imprisonment on children’s development. We contribute to this literature using data from the Fragile Families and Child Wellbeing Study to examine the effects of paternal incarceration on developmental and school readiness outcomes for approximately 3,000 urban children. We estimate cross-sectional and longitudinal regression models that control not only for fathers’ basic demographic characteristics and a rich set of potential confounders, but also for several measures of pre-incarceration child development, and family fixed effects. We find that paternal incarceration is positively associated with children’s externalizing problems at age five. Results are mixed with respect to attention problems, and we find some evidence that children of incarcerated fathers experience less anxiety than their peers. The observed effects of incarceration on child behavioral problems are significantly stronger than the effects of other forms of father absence, suggesting that children with incarcerated fathers may require specialized support from caretakers, teachers, and social service providers.Fragile families, childbearing, nonmarital childbearing, fartherhood, fathers, incarceration